2009
DOI: 10.1371/journal.pone.0006695
|View full text |Cite
|
Sign up to set email alerts
|

The Chemokine CXCL16 and Its Receptor, CXCR6, as Markers and Promoters of Inflammation-Associated Cancers

Abstract: Clinical observations and mouse models have suggested that inflammation can be pro-tumorigenic. Since chemokines are critical in leukocyte trafficking, we hypothesized that chemokines play essential roles in inflammation-associated cancers. Screening for 37 chemokines in prostate cancer cell lines and xenografts revealed CXCL16, the ligand for the receptor CXCR6, as the most consistently expressed chemokine. Immunohistochemistry and/or immunofluorescence and confocal imaging of 121 human prostate specimens sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(102 citation statements)
references
References 51 publications
5
95
1
1
Order By: Relevance
“…CXCL12 expression correlates well with lower apoptosis in human myelodysplastic syndrome [27]. Likewise, CCR6 and CXCR6 can promote the proliferation of colorectal cancer cells [28] and prostate cancer cells [29], respectively. Furthermore, phosphatidylinositol-3-kinase (PI3K)-mediated protection of tumor cells from apoptosis has been reported after CCR10 activation in melanoma [30] and CCR7 activation in squamous cell carcinoma of the head and neck [31] (Figure 1).…”
Section: Direct Effects On Cancer Cellsmentioning
confidence: 85%
“…CXCL12 expression correlates well with lower apoptosis in human myelodysplastic syndrome [27]. Likewise, CCR6 and CXCR6 can promote the proliferation of colorectal cancer cells [28] and prostate cancer cells [29], respectively. Furthermore, phosphatidylinositol-3-kinase (PI3K)-mediated protection of tumor cells from apoptosis has been reported after CCR10 activation in melanoma [30] and CCR7 activation in squamous cell carcinoma of the head and neck [31] (Figure 1).…”
Section: Direct Effects On Cancer Cellsmentioning
confidence: 85%
“…In human glioma, colorectal, breast and renal cancer, tumors with high CXCL16 expression had slower progression and showed infiltration of CD4 and CD8 lymphocytes [53][54][55][56][57]. On the contrary in prostate cancer CXCL16 expression has been correlated with poor prognosis [58]. Interestingly, it has been reported that ionizing radiation therapy markedly enhanced CXCL16 secretion by mouse and human breast cancer cells, which recruited CXCR6+ effector cells [55].…”
Section: Chemokine Regulation Of Leukocyte Attraction Within Tumorsmentioning
confidence: 99%
“…Coupled with their previous cell line studies, this result appears to corroborate the results of Ha et al (17) that CXCL16 and total CXCR6 mRNA expression are higher in more aggressive cancer cases. Other recent findings from studies of prostate cancer tissue have provided further confirmation that the CXCL16/CXCR6 expression level is closely associated with high malignant features, as observed with the Gleason grade and tumor stage in prostate cancer (25). Metastatic bone marrow, but not the liver and lung tissues, expressed higher levels of CXCL16 and total CXCR6 mRNA than the primary prostate cancer tissues, implying that the metastatic process was correlated with chemokines and its receptors (17).…”
Section: Discussionmentioning
confidence: 61%